Pengaruh Independensi, Kompetensi, Dan Pengalaman Kerja Auditor Terhadap Kualitas Audit - Caroline Sytha Sunarta; Suhajar Wiyoto (Universitas Multimedia Nusantara, 2012)
The objective of this research is to examine the effect of auditor’s independency, competency, and job experience towards audit quality.This research is conducted by using method survey to public accountants (external auditors) that working settled in Public Accountant Firm (KAP) in Jakarta and Tangerang, in 2012 and have one year minimum experience, as respondents with type research of causality. Using likert scale as an instrument (questionaire) for measure auditor’s perceptions about the independency, competency, and job experience that influence audit quality. From 150 questionaire distributed, returned was 109 questionaire, and 24 not complete, so that only 85 questionaire could be process. Data analysis conducted with multiple regression model. The hypotheses tested are revealed as that independency, competency, and job experience have influence to audit quality as well as partially and simultaneously. The result of the test showed empirical testimony that auditor’s independency, competency, and job experience as well as simultaneously significantly influence audit quality. Partially, independency, competency, and job experience also have significant influence to audit quality. Future research expected can extend survey area coverage and add more independent variables that can have influence to audit quality. Keywords: independency, competency, job experience, audit quality.